Emission Dispersion Pattern Analysis of Palm Oil Mill Boiler & Genset Chimneys Using AERMOD - Nasution, Renni Wardiah; Fitri, Yulia; Retnawaty, Sri Fitria; Fatiya; Putri, Reza Pratama; Daulay, Rosni Amelia (Photon: Jurnal Sain dan Kesehatan, 2026)
PT X is one of the palm oil mills located in the Tenayan Industrial Estate (KIT). Emission sources originate from boiler and generator stacks that produce PM, SO₂, NO₂, CO, and NOₓ. This study aims to analyze the direction of emission distribution from boiler and generator stacks using the AERMOD model. In addition, the study analyzes differences in emission distribution patterns during the dry and rainy seasons. Modeling was conducted using AERMOD by incorporating emission source parameters, meteorological data obtained from the Climate Data Store (CDS), and topographic data from Google Earth Pro. The modeling process consisted of AERMET, AERMAP, and AERMOD stages. The results indicate that the annual maximum concentrations of PM, SO₂, NO₂, CO, and NOₓ are 1,24 μg/m³, 2,17 μg/m³, 4,33 μg/m³, 0,0034 μg/m³, and 0,065 μg/m³, respectively. The annual emission distribution pattern extends toward the southwest, with seasonal variations observed between the dry and rainy seasons.